Development of Visuo-Auditory Integration in Space and Time - Gori, Monica; Sandini, Giulio; Burr, David (Frontiers in Integrative Neuroscience, 2012)
Adults integrate multisensory information optimally (e.g. Ernst & Banks, 2002) while children are not able to integrate multisensory visual haptic cues until 8-10 years of age (e.g. Gori, Del Viva, Sandini, & Burr, 2008). Before that age strong unisensory dominance is present for size and orientation visual-haptic judgments maybe reflecting a process of cross-sensory calibration between modalities. It is widely recognized that audition dominates time perception, while vision dominates space perception. If the cross sensory calibration process is necessary for development, then the auditory modality should calibrate vision in a bimodal temporal task, and the visual modality should calibrate audition in a bimodal spatial task. Here we measured visual-auditory integration in both the temporal and the spatial domains reproducing for the spatial task a child-friendly version of the ventriloquist stimuli used by Alais and Burr (2004) and for the temporal task a child-friendly version of the stimulus used by Burr, Banks and Morrone (2009). Unimodal and bimodal (conflictual or not conflictual) audio-visual thresholds and PSEs were measured and compared with the Bayesian predictions. In the temporal domain, we found that both in children and adults, audition dominates the bimodal visuo-auditory task both in perceived time and precision thresholds. Contrarily, in the visual-auditory spatial task, children younger than 12 years of age show clear visual dominance (on PSEs) and bimodal thresholds higher than the Bayesian prediction. Only in the adult group bimodal thresholds become optimal. In agreement with previous studies, our results suggest that also visual-auditory adult-like behaviour develops late. Interestingly, the visual dominance for space and the auditory dominance for time that we found might suggest a cross-sensory comparison of vision in a spatial visuo-audio task and a cross-sensory comparison of audition in a temporal visuo-audio task.